Peningkatan Kualitas Sumber Daya Manusia di Kelurahan Moncongloe melalui Program Kreatif Keislaman KKN VI STIBA Makassar - Ahmad Syaripudin; Akhmad Hanafi Dain Yunta (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
The purpose of implementing this KKN is as a form of community service by providing Islamic guidance and enlightenment to the residents of the Moncongloe Village, Moncongloe District. The method of implementing the KKN program begins with observing the condition of the community using SOAR analysis which then produces work programs and activities including: (1) Seminar on Socialization of Work Programs; (2) Signing of MoU on Cooperation in Religious Development; (3) Al-Qur'an teaching using the Dirosa method; (4) TPA development; (5) Teaching in elementary school; (6) Development of Mosque Youth; (7) Social Services; (8) Taklim Week on Islamic Materials; (9) Learning Police Taklim; (10) Lightning Islamic Boarding School; (11) Sole Children Festival; and (12) Tabligh Akbar Welcoming Ramadan. All of these programs were welcomed with great enthusiasm by the local community and succeeded in bringing about the expected changes. So that even though the Community Service Program has ended, changes in the attitude and behavior of the community's human resources are seen to be more religious in the religious field.